Impact of Urban Expansion on the Asset and Food Security Status of Peri-urban Farmers in Injibara Town, Amhara Region, Ethiopia - Guyalo, Amanuel; Meshesha, Yeshiwas (ETHIOINQUIRY Journal of Humanities and Social Sciences, 2025)
Both city administrators and academics studying urban and regional affairs have serious concerns about the issue of unchecked urban expansion and its inexorable effects on the peri-urban and rural areas, particularly in developing nations. Scientific studies that measure the actual impact of such expansion and provide national and local governments and other stakeholders with information are essential to at least limit the negative consequences. In order to estimate and quantify the impact of urban expansion on the asset and food security of peri-urban families, we, therefore, selected 283 households (130 displaced and 153 non-displaced) from Injibara city, one of the fastest-expanding townships in the Amhara region. We employed an endogenous switching regression approach, which is one of the increasingly popular techniques for resolving the selection bias issue in impact studies. Our findings show that urban expansion has a significant negative impact on the asset and food security status of peri-urban farmers and makes them worst off for being displaced. The adaptation of context-specific urban development and planning models is therefore necessary by city administrations, including major stakeholders, in order to create win-win scenarios and improve the livelihoods of both urban people and peri-urban farmers.